Klasterisasi Faktor Orang Tua Dalam Memilih Sekolah Taman Kanak-Kanak Menggunakan Algoritma K-Means Clustering (Studi Kasus : TK Aek Litta) - Diffri Solihin Siregar; Billy Hendrik (Lembaga Pengembangan Kinerja Dosen, 2023)
School is a place where students are taught under the guidance of teachers. Schools have an important role in developing children's intellectual capacity because school is a place where children look for information and hone their skills. Choosing a school that suits your child's character is very important. Children need kindergarten education to develop their character and personality and to prepare themselves for entering elementary school. There are many things parents choose to do when choosing a school for their children, including: distance, facilities, curriculum, costs, etc. In this case, to find out the parents' factors in choosing a kindergarten school for their child, the author uses the K-Means algorithm to see the highest factors that make parents choose the Aek litta kindergarten school. K-Means separates data into groups according to how close each group is to a particular cluster. The results of the clustering process with 3 iterations stated that for cluster 1 there were 7 parents who had similar factors in choosing Aek Litta Kindergarten, for cluster 2 there were 3 parents with similar factors.